ANALISIS NPL, LIKUIDITAS DAN RENTABILITAS TERHADAP CAR PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dera Putri Irawati; Siregar, Dian Lestari (LPPM Universitas Putera Batam, 2022)
A healthy bank activity is the bank's ability to use and control its funds, both from owner funds and funds from outside parties such as customers, so that the bank can run well. So that the aspect of capital adequacy becomes an important role in the operational activities of a bank. This study aims to determine the effect of NPL, Liquidity and Profitability on CAR at banks listed on the Indonesia Stock Exchange. This research was conducted using quantitative methods using secondary data from the annual financial statements listed on the Indonesia Stock Exchange. From a population of 47 banking companies, a sample of 16 banking companies was obtained using purposive sampling method. In this study, the data analysis method used is the classical assumption test, multiple linear regression analysis, and hypothesis testing. Based on the results of the analysis that has been carried out, the results partially show that NPL and liquidity proxied by LDR have a positive and significant effect on CAR, while Profitability proxied by ROA has no significant effect on CAR. Simultaneous results show that NPL, LDR and ROA together have an effect on CAR.